2021
DOI: 10.1177/15593258211058028
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Selected Medicinal Plants Against Carrageenan Induced Inflammation in Rats

Abstract: The current study was aimed to analyze the therapeutic effect of selected medicinal plants, that is, Curcuma longa, Zingiber officinale, Trigonella graceum-foenum, Nigella sativa, and Syzygium aromaticum against carrageenan-induced oxidative stress and inflammation in rats. Phytochemical analysis revealed the presence of diverse range of bioactives. IC50 values for antioxidant assays including DPPH (2,2-diphenyl-1-picrylhydrazyl), metal chelating, ABTS scavenging (2, 2′-Azino-Bis-3-Ethylbenzothiazoline-6-Sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Habitat is an important factor affecting the quality of herbal medicinal materials. Different habitats will affect the formation and accumulation of secondary metabolites in the plants, thereby affecting the quality of medicinal products [ 10 , 11 ]. Therefore, the significant differences in the contents of total flavonoids and total sterols and the expression of the 53 metabolites that we found in this study might be the result of field management and habitat differences.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat is an important factor affecting the quality of herbal medicinal materials. Different habitats will affect the formation and accumulation of secondary metabolites in the plants, thereby affecting the quality of medicinal products [ 10 , 11 ]. Therefore, the significant differences in the contents of total flavonoids and total sterols and the expression of the 53 metabolites that we found in this study might be the result of field management and habitat differences.…”
Section: Discussionmentioning
confidence: 99%
“…Phytobioactives are also known as plant secondary metabolites and bioactive compounds (Fatima et al, 2021). They are present ubiquitously in the plant kingdom and are considered nonnutritional but vital components for the maintenance of human health (Nafees et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Phytobioactive compounds play a significant role in the adaptation of plants to their surrounding environment but are also a major source for the pharmaceutical industry (Merrouni & Elachouri, 2021 ). Phytobioactives are also known as plant secondary metabolites and bioactive compounds (Fatima et al, 2021 ). They are present ubiquitously in the plant kingdom and are considered nonnutritional but vital components for the maintenance of human health (Nafees et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 An antiinflammatory effect of the extract of J. nigra leaf has been reported in some animal models of acute and chronic inflammation, such as carrageenan-induced mice hind paw edema, 15 xylene-induced mice ear edema, 16 and cotton pellet-induced granuloma tests in mice. 17 Also, it was shown that the extract reduced nociception in models of acute pain in mice, such as the hot-plate and the writhing tests, 15 , 16 but the effect of the extract has not been investigated in other models of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Acute inflammation is associated with increased production of reactive oxygen and nitrogen species, inflammatory mediators, and the activation of enzymes. 17 , 18 Pain is commonly associated with inflammation, which is the consequence of tissue damage, chemical stimuli, and foreign substances. After tissue injury, nitroxidant dysregulation in the cell promotes the development of inflammation and central sensitization, crucial for the onset of chronic neuropathic or inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%